2018
DOI: 10.1080/10837450.2018.1534861
|View full text |Cite
|
Sign up to set email alerts
|

Development of a small-scale spray-drying approach for amorphous solid dispersions (ASDs) screening in early drug development

Abstract: Development of a small-scale spray-drying approach for amorphous solid dispersions (ASDs) screening in early drug developmentThe present study details the development of a small-scale spray-drying approach for the routine screening of amorphous solid dispersions (ASDs). This strategy aims to overcome the limitations of standard screening methodologies like solvent casting and quench cooling to predict drug-polymer miscibility of spraydried solid dispersions (SDSDs) and therefore to guarantee appropriate carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…DOE modeling was conducted by using the custom design platform in JMP 16 software developed by the SAS institute. As seen in Table , each process factor was studied at four levels while the inner needle diameter was included in the DoE as a numerical factor (two levels) . The model parameters specified as a traditional response surface design (RSM) are listed as applied voltage (kV) and RS, flow rate (mL/h) and RS, gap distance (cm) and RS, nozzle diameter (gauge), applied voltage (kV)·applied voltage (kV), applied voltage (kV)·flow rate (mL/h), flow rate (mL/h)·flow rate (mL/h), applied voltage (kV)·gap distance (cm), flow rate (mL/h)·gap distance (cm), gap distance (cm)·gap distance (cm), applied voltage (kV)·nozzle diameter (gauge), flow rate (mL/h)·nozzle diameter (gauge), and gap distance (cm)·nozzle diameter (gauge).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DOE modeling was conducted by using the custom design platform in JMP 16 software developed by the SAS institute. As seen in Table , each process factor was studied at four levels while the inner needle diameter was included in the DoE as a numerical factor (two levels) . The model parameters specified as a traditional response surface design (RSM) are listed as applied voltage (kV) and RS, flow rate (mL/h) and RS, gap distance (cm) and RS, nozzle diameter (gauge), applied voltage (kV)·applied voltage (kV), applied voltage (kV)·flow rate (mL/h), flow rate (mL/h)·flow rate (mL/h), applied voltage (kV)·gap distance (cm), flow rate (mL/h)·gap distance (cm), gap distance (cm)·gap distance (cm), applied voltage (kV)·nozzle diameter (gauge), flow rate (mL/h)·nozzle diameter (gauge), and gap distance (cm)·nozzle diameter (gauge).…”
Section: Methodsmentioning
confidence: 99%
“…As seen in Table 2, each process factor was studied at four levels while the inner needle diameter was included in the DoE as a numerical factor (two levels). 28 The model parameters specified as a traditional response surface design (RSM) are listed as applied voltage (kV) and RS, flow rate (mL/h) and RS, gap distance (cm) and RS, nozzle diameter (gauge), applied voltage (kV)•applied voltage (kV), applied voltage 3) were collected using a modular NicoletTM iSTM 50 FTIR system (ThermoFisher Scientific, Waltham, Massachusetts, USA). About 20−25 mg of the samples were analyzed for percentage transmittance from 4000 to 400 cm −1 at a resolution of 4 cm −1 and 64 scans per run.…”
Section: Design Of Experimental (Doe) Definitive Screening Designmentioning
confidence: 99%
“…Forster et al have reported the composition dependent presence of single or multiple T g values in the system of lacidipine and indomethacin with PVP . Apart from the presence of multiple T g values, reports also state the presence of a single T g as a sign of the molecularly dispersed ASD. , This is one of the commonly used qualitative predictors of drug-polymer miscibility with more than 50 instances in the reviewed literature. In a most recent report, Blasi et al have reported the presence of multiple T g values for ASD with ketoprofen content more than 35% w/w in poly­(D, L-lactide- co -glycolide) …”
Section: Methods For the Evaluation Of Drug-polymer Solubility And Mi...mentioning
confidence: 99%